PERKEMBANGAN ILMU ADMINISTRASI DAN FUNGSINYA UNTUK MENDUKUNG PERKEMBANGAN ILMU ADMINISTRASI - Nurhapani Nurhapani (Lembaga Penelitian dan Penerbitan Hasil Penelitian Ensiklopedia, 2020)
Administration etymologically comes from English, namely administration or to administear, which means to manage or to direct. Administration in the strict sense is administrative activities such as writing, writing, correspondence. administration is a collaborative activity of two or more people in achieving an activity of cooperation of two or more people in achieving a predetermined goal. Administration cannot be separated from daily life because humans are social creatures who cannot work alone and need others to achieve their goals. For this to achieve a predetermined goal, it requires the ability and motivation to encourage people and themselves to carry out and move a government organization.